Intractable Vomiting: An Interesting Case - Khyati Thapliyal; Ashutosh Garg; Vivek Pal Singh (Indian Journal of Medical Specialities)
Nausea and vomiting constitute one of the most common presenting symptoms in a variety of diseases in clinical practice. Recurrent vomiting can be due to simple gastritis which may lead to dehydration and electrolyte disturbances to threatening intracranial hypertension. Prolonged recurrent vomiting can also lead to malnutrition. Esophageal dysmotility is usually associated with dysphagia but is infrequently associated with recurrent vomiting. We report a case of acute-onset intractable vomiting in a 50-year-old Indian female who presented with severe dehydration and hypernatremia. A timed barium esophagogram revealed dilated esophagus with a rat-tail appearance. Upper gastrointestinal endoscopy revealed dilated esophagus with a tight esophageal-gastric junction. With a diagnosis of achalasia cardia, the patient underwent peroral endoscopic myotomy with complete resolution of symptoms.